Intercultural communication in Muslim societies - Hussain, Mohd. Yusof (IIUM Press, 2009)
The book contains a collection of eleven essays on a wide range of topics related to intercultural communication in Muslim societies. The topics includes the meaning and purpose of intercultural communication, qualities of a good intercultural communicator, the language of intercultural communication, the content of intercultural communication, barriers in intercultural communication and principles and practices of intercultural communication. The purpose of the book is to give readers a general understanding of intercultural communication, a subject that is gaining in importance throughout the Muslim world.